KONSEP PENDIDIKAN AKHLAK MENURUT IBN MISKAWAIH DAN ARISTOTELES (STUDI KOMPARATIF) - Bunyamin, Bunyamin (Universitas Muhammadiyah Prof Dr Hamka, 2018)
This research focuses to explore the concept of moral education according to ibn Miskawih and Aristoteles. What are the similarities and differences in their opinions about morals education?. The main aspect of human self development is morality, namely the source of human behaviour that applied in everyday life. This research uses qualitative methods while the type of research is library research. Research is carried out based on the literature review. The results of the study is that the concept of ahlak education according to Ibn Miskawih an Aristoteles is related to character, soul and virtue, goodness and happiness, virtue and midpoint, early age education and akhlak purpose. The equality of the two concepts is that akhlak education is based on the soul of each individual. The difference is in describing the character, a tool to measure the middle attitude and middle position. Keywords; concept of Education, Morality, Ibn Miskawaih, Aristoteles